Realization of Polaritonic Topological Charge at Room Temperature Using Polariton Bound States in the Continuum from Perovskite Metasurface (Advanced Optical Materials 6/2022). Issue 6 (18th March 2022) - Dang, Nguyen Ha My; Zanotti, Simone; Drouard, Emmanuel; Chevalier, Céline; Trippé‐Allard, Gaëlle; Amara, Mohamed; Deleporte, Emmanuelle; Ardizzone, Vincenzo; Sanvitto, Daniele; Andreani, Lucio Claudio; Seassal, Christian; Gerace, Dario; et al.
Abstract : In article number 2102386, Hai Son Nguyen and co‐workers demonstrate experimentally polariton bound states in the continuum ("pol‐BICs") in an excitonic metasurface based on 2D halide perovskite. These hybrid light–matter states, operating at room temperature, exhibit all peculiar features of BICs: a total uncoupling from the radiative continuum associated to an infinite radiative quality factor, and a topological charge associated to a polarization singularity in the farfield emission.